Uses of Antibiotics in Ornamental Fish in Hong Kong and the Antibiotic Resistance in the Associated Zoonotic Pathogens - Chun Au-Yeung; Kit-Ling Lam; Ka-Wai Chan; Wing-Yin Mo (MDPI AG, 2022)
The use of antibiotics in ornamental fish is not regulated, as they are not intended for human consumption. Although antibiotic resistant bacteria have been detected in ornamental fish worldwide, there have been no studies to look at the situation in Hong Kong. Therefore, the present study was conducted to investigate the use of antibiotics in ornamental fish. Ornamental fish were purchased from five local pet fish shops and the antibiotics in carriage water were quantified using liquid chromatography tandem mass spectrometry. Moreover, Aeromonas and Pseudomonas spp. present in carriage water were isolated and their minimum inhibitory concentrations against selected antibiotics were determined. Results indicated that among the twenty antibiotics screened, doxycycline (0.0155-0.0836 µg L−1), oxytetracycline (0.0102-29.0 µg L−1), tetracycline (0.0350-0.244 µg L−1), enrofloxacin (0.00107-0.247 µg L−1), and oxalinic acid (n.d.−0.514 µg L−1) were detected in all sampled shops. Additionally, MIC results revealed that some of the Aeromonas and Pseudomonas spp. isolates were highly resistant to all antibiotics selected. Our findings confirmed that multiple antibiotics are being used in ornamental fish and the associated bacteria are resistant to selected antibiotics, suggesting that this could be a significant transmission route of antibiotic resistant bacteria to household indoor environments.